2004
DOI: 10.1152/ajpheart.00529.2003
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of vascular function using strain-gauge plethysmography: technical considerations, standardization, and physiological findings

Abstract: The main purpose of the present study was to examine the relationships between measures of fitness [estimated peak oxygen consumption (V(O2) peak) and handgrip strength] and forearm vascular function in 55 young (22.6 +/- 3.5 yr) adults. In addition, the present study considered methodological and technical aspects regarding the examination of the venous system using mercury in-Silastic strain-gauge plethysmography (MSGP). Forearm venous capacitance and outflow were examined using five different [7, 14, 21, 28… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
3
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 43 publications
4
46
3
1
Order By: Relevance
“…In contrast, both KE and KF were significantly related to the VO t1/2 . These findings further confirm data from our laboratory suggesting that muscular fitness is related to venous function [31]. The associations suggest the contribution of the venous system to physical function is beyond the typical role as a "passive volume reservoir".…”
Section: Associations Between Vascular and Physical Functionsupporting
confidence: 88%
“…In contrast, both KE and KF were significantly related to the VO t1/2 . These findings further confirm data from our laboratory suggesting that muscular fitness is related to venous function [31]. The associations suggest the contribution of the venous system to physical function is beyond the typical role as a "passive volume reservoir".…”
Section: Associations Between Vascular and Physical Functionsupporting
confidence: 88%
“…Therefore, statistical analysis is performed in 16 patients treated with L-arginine and 14 patients treated with placebo. The sample size of patients for each group was estimated taking advantage of previous studies in which reactive hyperemia of FBF marker of endothelial vasodilation [11][12][13] was evaluated after long-term oral administration of L-arginine (6 g daily, 6 months). Therefore, we have designed the study to be large enough to be able to detect, with a β = 80% and α = 5%, an increase in reactive hyperemia of FBF from 5% with placebo to 30% with L-arginine treatment; and we evaluated that the final sample for each group was at least 14 patients.…”
Section: Patients and Study Designmentioning
confidence: 99%
“…Three plethysmographic measurements were averaged to obtain FBF at baseline and during reactive hyperemia [17]. This method has been recently validated, and results are reported in Alomari et al [18]. Moreover, it was demonstrated that the measurement of endothelial function by strain gauge plethysmography has a high correlation with brachial artery ultrasound [19].…”
Section: Patients and Study Designmentioning
confidence: 99%